What You Don't See : Cass Raines # 3 - Clark, Tracy, 1961- (New York, NY : Kensington Books, 2020)
"Wealth. Power. Celebrity. Vonda Allen's glossy vanity magazine has taken the Windy City by storm, and she's well on her way to building a one-woman media empire. Everybody adores her. Except the people who work for her. And the person who's sending her flowers with death threats ... As Vonda's bodyguard, off-duty cop Ben Mickerson knows he could use some back-up--and no one fits the bill better than his ex-partner on the police force, Cass Raines. Now a full-time private eye, Cass is reluctant to take the job. She isn't keen on playing babysitter to a celebrity who's rumored to be a heartless diva. But as a favor to Ben, she signs on. But when Vonda refuses to say why someone might be after her, and two of her staff turn up dead, Ben and Cass must battle an unknown assailant bent on getting to the great lady herself, before someone else dies. Cass finds out the hard way just how persistent a threat they face during the first stop on Vonda's book tour. As fans clamour for her autograph, things take an ugly turn when a mysterious fan shows up with flowers and slashes Ben with a knife. While her ex-partner's life hangs in the balance, Cass is left to find out what secrets Vonda is keeping, who might want her dead, and how she can bring Ben's attacker to justice before enemies in the Chicago Police Department try to stop her in her tracks . . ."--Provided by publisher.
Keywords: Raines, Cass -- (Fictitious character) -- Fiction; Women private investigators -- Illinois -- Chicago -- Fiction; African American private investigators -- Illinois -- Chicago -- Fiction; Women periodical editors -- Fiction; Celebrities -- Fiction; Bodyguards -- Fiction; Murder -- Investigation -- Illinois -- Chicago -- Fiction; Threats of violence -- Fiction; African American private investigators; Threats of violence; Women periodical editors; Women private investigators -- Fiction; Periodical editors -- Fiction; FICTION -- Mystery & Detective -- Private Investigators; FICTION -- Mystery & Detective -- Women Sleuths; FICTION -- Thrillers -- Suspense; Celebrities; Bodyguards; Murder -- Investigation; Women private investigators; Bodyguards -- Fiction; Homicide -- Fiction; Chicago (Ill.) -- Fiction; Illinois -- Chicago; Chicago (Ill.) -- Fiction; Detective and mystery stories; Detective and mystery fiction; Fiction; Thriller fiction; Detective fiction; Mystery fiction